Promoting intra-regional trade in South Asia through trade facilitation measures under the auspices of the South Asian association for regional cooperation - Islam, Md Rizwanul (© 2014 Brill, 2016)
This book chapter was published in the Regional Cooperation and Free Trade Agreements in Asia [© 2014 Brill ] and the definite version is available at : http://doi.org/10.1163/9789004279902_014